In vitro antimicrobial activity on clinical microbial strains and antioxidant properties of Artemisia parviflora - Ahameethunisa Abdul R; Hopper Waheeta (BMC, 2012)
Abstract Background Artemisia parviflora leaf extracts were evaluated for potential antimicrobial and antioxidant properties. Antimicrobial susceptibility assay was performed against ten standard reference bacterial strains. Antioxidant activity was analyzed using the ferric thiocyanate and 2, 2-Diphenyl-1-Picrylhydrazyl (DPPH) assays. Radical scavenging activity and total phenolic content were compared. Phytochemical analyses were performed to identify the major bioactive constitution of the plant extract. Results Hexane, methanol and ethyl acetate extracts of A. parviflora leaves exhibited good activity against the microorganisms tested. The n-hexane extract of A. parviflora showed high inhibition of the growth of Pseudomonas aeruginosa, Escherichia coli and Shigella flexneri. Methanol extract showed strong radical scavenging and antioxidant activity, other extracts showed moderate antioxidant activity. The major derivatives present in the extracts are of terpenes, steroids, phenols, flavonoids, tannins and volatile oil. Conclusions The results obtained with n-hexane extract were particularly significant as it strongly inhibited the growth of P. aeruginosa, E. coli and S. flexneri. The major constituent of the n-hexane extract was identified as terpenes. Strong antioxidant activity could be observed with all the individual extracts. The antimicrobial and antioxidant property of the extracts were attributed to the secondary metabolites, terpenes and phenolic compounds present in A. parviflora and could be of considerable interest in the development of new drugs.